Decision algorithm and surgical strategies for managing tracheocutaneous fistula - Kao, Chieh-Ni (J Thorac Dis, 2020)
BACKGROUND: Persistent tracheocutaneous fistula (TCF) is a complication of prolonged use of tracheostomy tube. Although many procedures exist to correct this issue, there is no consensus regarding its optimal management. We constructed a decision algorithm to determine appropriate surgical strategies for TCF repair. METHODS: Retrospectively reviewing our hospital’s records, we found fourteen consecutive patients who had received surgical repair of tracheocutaneous fistula (primary closure or advanced local flap) between February 2013 and December 2018 and collected data relevant to their cases. RESULTS: We identified 11 male and 3 female patients. Duration of tracheostomy dependence was 8.1±4.7 months, and timespan from decannulation to surgical closure 7.4±6.5 months. Seven patients received primary closures, six received hinged turnover flaps, and one received random and perforator flap reconstruction. There was no perioperative mortality or morbidity except for one patient requiring a repeat tracheostomy 11 months after TCF repair due to pneumonia and subsequent respiratory failure. We used our findings and those reported in the literature to construct a modified risk factor scoring system based on patient’s physical status, major comorbidities, perifistular soft tissue condition, and nutritional status and an algorithm for managing TCF based on the patients’ fistula size and modified risk factor scores. CONCLUSIONS: In conclusion, we were able to review our cases and those of other studies to create a risk scoring system and a decision algorithm that we believe will help optimize patient-directed surgical management of TCF repair.